(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Poverty is a problem in various parts of the world, which is caused by various factors such as the unemployment rate which is still very high so that the workforce is not absorbed enough, because investment is still lacking and many more. So research This will determine the impact of unemployment, the labor force and investment on the poverty in Bengkulu. The method used by this research is multiple linear regression with panel data. This type of research is quantitative descriptive with secondary data. The results of the research show that if the unemployment rate is reduced it will have a significant influence on poverty in Bengkulu province, if the level of labor force participation continues to be increased it will have a significant influence on poverty, and if investment is increased it will reduce the poverty level in province Bengkulu.